Efficacy and Safety of Anti-Tumor Necrosis Factor-Α Biosimilars in Rheumatological Practice and Their Registration, Patenting - Elena Litvinova (Journal of Global Pharma Technology, 2020)
The aim of the work is to analyze and systematize data regarding the efficacy and safety of anti-tumor necrosis factor-α biosimilars, as well as their registration and patenting. Studies were conducted using a databases on the Internet: Ukrainian patent office, the European patent office, the US patent office, the Food and drug administration, European Medicines Agency, State enterprise “The State Expert Center” of Ukraine. The breakthrough in the treatment of rheumatoid arthritis is the discovery and administration of anti-TNF-α agents, such as infliximab, adalimumab, etanercept, certolizumab pegol, golimumab. Numerous randomized clinical trials and meta-analysis data indicate high efficacy and acceptable safety of anti-TNF-α biosimilars for the treatment of rheumatoid arthritis. The development and registration of anti-TNF-α biosimilars reduces the costs of health care and patients for biological therapy, increases patient access to treatment with the latest drugs, and contributes to the further development of biotechnology. Thus, effective anti-tumor necrosis factor-α biosimilars may be more accessible to the general population with rheumatoid arthritis. Despite certain hazards and risks associated with possible violations in the implementation of biological products in real practice, the industry of highly effective biosimilars brings progress both for the development of science and for practical healthcare.Keywords: infliximab, adalimumab, etanercept, certolizumab pegol, golimumab, biosimilar, efficacy, patent.